Sexual Division in Parenting: A Normative Context That Hinders Co-Responsibility - García de Diego, José María; García-Faroldi, Livia (Sage Journals, 2022)
Recent decades have seen an increase in women’s employment rates and an expansion of egalitarian values. Previous studies document the so-called “motherhood penalty”, which makes women’s employment more difficult. Demands for greater shared child-rearing between parents are hindered by a normative climate that supports differentiated gender roles in the family. Using data from the Center for Sociological Research [Centro de Investigaciones Sociológicas] (2018), this study shows that the Spanish population perceives that differentiated social images of motherhood and fatherhood still persist. The “sexual division in parenting” index is proposed and the profile of the individuals who most perceive this sexual division is analyzed. The results show that women and younger people are the most aware of this social normativity that unequally distributes child care, making co-responsibility difficult. The political implications of these results are discussed.
Keywords: Política familiar; Madres trabajadoras; Mothering; Fathering; Socialization; Family roles; Gender culture; Gender roles